Influenza B-Associated Atypical Hemolytic Uremic Syndrome - Mano, L (2018)
Introduction: Influenza A infections have been described to cause secondary hemolytic uremic syndrome and to trigger atypical hemolytic uremic syndrome (aHUS) in individuals with an underlying genetic complement dysregulation. To date, Influenza B has only been reported to trigger aHUS in 2 patients. In 61% of aHUS cases, mutations are found in H, B and I factors, membrane cofactor protein (MCP), C3 and thrombomodulin. MCP (CD46) mutations account for 10-15% of cases. Clinical Case: A 13-year-old boy was transferred to a terciary pediatric centre with acute renal lesion in the context of HUS. Evidence was found for Influenza B infection and results for other etiologic agents were negative. He was treated with Oseltamivir for 5 days. Etiologic study revealed decreased C ́3 (0,81 g/L), normal C ́4 (0,27 g/L) and all antibodies were negative: anti-Beta2 GP1 IgG / IgM, anti-cardiolipine IgG / IgM, anti-neutrophil-citoplasm-PR3 and MPO. Alternate complement pathway study (AH 50) were 112 % of normal value (reference value >70%) and ADAMTS 13 activity were 0.79 (values above 0.67 may be found in aSHU as well as other microangiopathic trombopathies). Molecular study of complement including 11 genes (CFH, CD46 (MCP), CFI, C3, THBD, CFB,CFHR5, CFHR1 CFHR3, CFHR4, DGKE) found a pathogenic heterozygotic missense variant on CD46 (MCP) gene, c.554A>G, p.Asp185Gly, associated with aHUS. Conclusions: aHUS patients should be screened for all known disease-associated genes. Screening should not be stopped after finding a mutation to avoid missing other genetic susceptibility factors influencing disease phenotype, particularly in patients with MCP or CFI mutations, because they have a higher probability of also carrying mutation in another gene than patients with CFHor C3 mutations. Influenza B is a trigger for aHUS and might be underreported as such. Influenza vaccination may protect patients at risk.